Omphalocele and Intrauterine Growth Restriction, an Unusual Association of two Congenital Syndromic Malformations - Albu, Dinu-Florin; Albu, Cristina-Crenguta; Albu, Stefan-Dimitrie (International Journal of Medical Research and Review, 2015)
We report a case of a 30 year old pregnant woman. Ultrasound examination showed severe intrauterine growth restriction (IUGR) and an omphalocele. Amniocentesis was performed and the fetal chromosomal analysis showed mosaic trisomy 18. Further genetic investigations were done. The pregnancy was terminated one week later. Autopsy confirmed the ultrasound images findings. Our presentation is a very rare case report of mosaic trisomy 18, prenatal diagnosis, with important an anusual association of two congenital malformation, omphalocele and intrauterine severe growth restriction.